The ASQ certified manager of quality/organizational excellence handbook - Wood, Douglas C., 1955-; Furterer, Sandra L.; Craddock, Bill (ASQExcellence, 2021)
"This handbook is a comprehensive reference source designed to help professionals address organizational issues from the application of the basic principles of management to the development of strategies needed to deal with the technological and societal concerns of the new millennium. The content of this fourth edition has been revised to reflect a more current global perspective and to align with the 2014 Certified Manager of Quality/Organizational Excellence (CMQ/OE) Body of Knowledge (BoK). In order to provide a broad perspective of quality management, this book has specifically been written to address: Historical perspectives relating to the evolution of particular aspects of quality management, including recognized experts and their contributions Key principles, concepts, and terminology relevant in providing quality leadership, and communicating quality needs and results Benefits associated with the application of key concepts and quality management principles Best practices describing recognized approaches for good quality management Barriers to success, including common problems that the quality manager might experience when designing and implementing quality management, and insights as to why some quality initiatives fail Guidance for preparation to take the CMQ/OE examination. Organized to follow the BoK exactly, throughout each section of this handbook the categorical BoK requirements associated with good quality management practices for that section are shown in a box preceding the pertinent text. These BoK requirements represent the range of content and the cognitive level to which multiple-choice questions can be presented. Although this handbook thoroughly prepares individuals for the ASQ CMQ/OE exam, the real value resides in post-exam usage as a day-to-day reference source for assessing quality applications and methodologies in daily processes. The content is written from the perspective of practitioners, and its relevance extends beyond traditional product quality applications"-- Provided by publisher.
Keywords: Total quality management -- Handbooks, manuals, etc.; elektronické knihy; electronic books